RANCANG BANGUN SISTEM INFORMASI PENEMPATAN KERJA BERBASIS WEB DI POLITEKNIK LP3I JAKARTA KAMPUS SUDIRMAN TANGERANG - Karnoto Hanif; Randi Apriliyadi Rahmat (POLITEKNIK LP3I JAKARTA, 2024)
Placement is the process of assigning or filling positions or reassigning employees to new or different tasks or positions. This assignment can be the first assignment for newly recruited employees, but it can also be through promotion, transfer, demotion, or even termination of employment. In this case, C&P, as the division handling job placement, experienced difficulties because all stages of placement and recording were still very manual. Therefore, the author conducted observations from January 2022 at the LP3I Jakarta Polytechnic, Sudirman Campus, Tangerang, with the aim of simplifying the job placement recording process by developing a web-based job placement information system, which has the advantage of being accessible anywhere and is more efficient because it does not use paper or Excel, which must be managed manually. The author used the Laravel framework, built with the Visual Studio Code editor, which is a cutting-edge technology at the time this report was written.